“Elaboración de un manual de buenas prácticas de manufactura, para el proceso de helados artesanales de pancali s.a. 2013.” - Carrión Abad, Diana Elizabeth (2015)
This work in the city of Guayaquil, arises when the company Pancali SA in view of its strong growth over the years decided to start the project of creating a line of Artisan Ice Cream, seeking to innovate the range of products it offers its customers and the market in general.